A comparison of high thoracic epidural anaesthesia versus conventional intravenous opioids in pediatric patients undergoing corrective open heart surgery for ventricular septal defect - Singh, Kshetrimayum Sandeep Kumar; Sharma, Vipul K.; Shouche, Sachin; Sasidharan, Shibu; Dhillon, Gurpreet Kaur (International Journal of Advances in Medicine, 2021)
Background: We compared high thoracic epidural anaesthesia with a combination of morphine and bupivacaine versus IV fentanyl as an alternative for perioperative pain management. Methods: Group-E: Injection Morphine 75-100 mcg/kg and Injection 0.25 % Bupivacaine 0.5 ml/kg was given via epidural catheter at insertion, Injection 0.25% Bupivacaine 0.5 ml/kg just before skin incision, and continuous infusion of Injection 0.125% Bupivacaine at 0.2 ml/kg/hr intra-operatively. Post-operative 0.1 ml/kg/hr infusion. Group F- intravenous fentanyl 2-3 mcg/Kg IV bolus given just before skin incision, followed by 1-2 mcg/Kg/hr IV fentanyl started after weaning from cardiopulmonary bypass. Results: The mean ScvO2 was comparable between the two groups during induction period but became higher in group E during bypass and post bypass period intraoperatively, and the difference in rise in ScvO2 is statistically significant with a p<0.05. The mean rSo2- C was comparable between the two groups in the first postoperative hour but group F shows higher rSo2-C postoperatively which was statistically significant. The postoperative pain was significantly lower in group E in the postoperative period (except for 4,5,6 and 40 and 48th hour). Conclusions: HTEA to paediatric patients prior to sternotomy for cardiac surgeries resulted in a much better control of haemodynamic parameters. Produces better central venous and regional tissue oxygenation during bypass and post bypass intraoperatively as compared to the patients that received only intravenous fentanyl. There was lower amount of postoperative bleeding in the HTEA group with significant reduction in requirement of post-operative ventilation and time to extubation after surgery, better post-operative pain control and overall outcome.